Under what conditions would a strike be illegal - Abdul Kadir, Adibah; Tasmin, Rosmaini; Ismail, Fadillah; Abdul Hamid, Nor Aziati (Penerbit Uthm, 2019)
Strike can be characterised by the Industrial Relations Act (Section 2) is "The discontinuance of work by a group of labourers acting in mix, or a purposeful refusal or a refusal under a typical comprehension of various workers to proceed with work or to acknowledge business, and incorporates any demonstration or oversight by an assortment of workers acting in mix or under a typical comprehension, which is expected to or results in an impediment, confinement, decrease or suspension of a laziness in the execution or execution of the entire or any piece of the obligations associated with their business", (Aminuddin, 2016).